2013
DOI: 10.1007/s12262-013-0855-y
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Total Colectomy on Bacterial Translocation in a Model of Acute Pancreatitis

Abstract: Prevention of secondary infection is currently the main goal of treatment for acute necrotizing pancreatitis. Colon was considered as the main origin of secondary infection. Our aim was to investigate whether prophylactic total colectomy would reduce the rate of bacterial translocation and infection of pancreatic necrosis. Forty-two Sprague-Dawley rats were used. Pancreatitis was created by ductal infusion of sodium taurocholate. Rats were divided into four groups: group-1, laparotomy + pancreatic ductal infus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…After incubation at 37°C for 72 hours in aerobic atmosphere, the colony‐forming units (CFUs) were counted in each plate. Positive results were determined if bacterial counts were higher than 1000 CFU/g …”
Section: Methodsmentioning
confidence: 99%
“…After incubation at 37°C for 72 hours in aerobic atmosphere, the colony‐forming units (CFUs) were counted in each plate. Positive results were determined if bacterial counts were higher than 1000 CFU/g …”
Section: Methodsmentioning
confidence: 99%
“…High-throughput 16S rDNA sequencing of the small intestine, colon and feces Previous studies reported gut-derived bacteria overgrowth and higher intestinal colonization of Gram negative bacteria occurs in AP rat models by conventional culture techniques. 20,21 However, 80% of gut bacteria are novel species that cannot be cultivated, and only 20% of intestinal microbiota can be iden-tied using culture-based methods. 22 Furthermore, although polymerase chain reaction (PCR) has been used to identication of bacterial DNA in blood samples, it fails to detect several microorganisms in a single specimen.…”
Section: Ap Induced Pancreatic Injurymentioning
confidence: 99%
“…Previous studies have provided a detailed description on the characteristic of bacterial species in patients and rats with AP. [14][15][16] In detail, the paper of Li et al, provided a detailed description on the features of bacterial species and the prevalence of bacteremia in patients with AP. 14 Şenocak et al, proved that prophylactic total colectomy was associated with elevated bacterial translocation to the pancreas in AP rats.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study suggested that prophylactic total colectomy in patients with AP induces SIBO involving both Gram-negative bacilli ( Escherichia coli , Proteus spp.) and anaerobic bacteria[ 9 ]. We performed the present study to investigate the incidence of SIBO in AP with different severity grades and explore the correlation between SIBO and complications of AP.…”
Section: Introductionmentioning
confidence: 99%